Drug Courts and Net-Widening in U.S. Cities: A Reanalysis Using Propensity Score Matching - Lilley, David R. (Criminal justice policy review, 2020)
Although drug courts were intended to reduce the justice system involvement of drug offenders, a recent study found evidence that drug courts were associated with increased (rather than decreased) arrests for minor misdemeanor drug offenses (Lilley, 2017; Walsh, 2011). However, the previous study did not utilize an equivalent comparison group and may have relied on a large sample size to generate findings. The current study tested the robustness of those findings by analyzing only cities with over 50,000 population, including four additional years of data, and utilizing a more equivalent comparison group that was propensity-matched to reduce the possibility that a preexisting difference may have generated higher arrest outcomes among drug court jurisdictions. Net-widening, arrest, and crime challenges and implications for drug court policies and law enforcement roles are also discussed.